Martyrs, memory and misrepresentation: The Spanish Catholic Church, religious persecution and the Spanish Civil War. (1st September 2018) - Thomas, Maria
This article explores the ways in which the victims of anticlerical violence during the Spanish Civil War have been represented and remembered by the Spanish ecclesiastical hierarchy and Catholic hagiographers, examining the period from the Spanish Civil War up to the present day. It sustains that the discourse of martyrdom forged by the Catholic Church during the Civil War and the Dictatorship played a crucial role in legitimating the rebel war effort and the Franco Dictatorship, and in justifying repression against those associated with the Second Republic. It argues that the key tenets of the martyrdom discourse survived the Transition to Democracy and continue to characterize present-day Spanish ecclesiastical discourse. Against this backdrop, a re-evaluation of the Spanish episcopate's assertions that the martyrs of the Civil War are non-political symbols of reconciliation between Spaniards is necessary.